2022
DOI: 10.3390/molecules27175543
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment with Melatonin Improves Hippocampal Neurogenesis in the Aged Brain and Under Neurodegeneration

Abstract: Adult hippocampal neurogenesis is altered during aging and under different neuropsychiatric and neurodegenerative diseases. Melatonin shows neurogenic and neuroprotective properties during aging and neuropathological conditions. In this study, we evaluated the effects of chronic treatment with melatonin on different markers of neurodegeneration and hippocampal neurogenesis using immunohistochemistry in the aged and neurodegenerative brains of SAMP8 mice, which is an animal model of accelerated senescence that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…Данный эффект блокируется конкурентным антагонистом рецепторов мелатонина, люзиндолом, в частности в нервных стволовых клетках и плюрипотентных стволовых клетках [29]. На уровне тотипотентных стволовых клеток действие МТ реализуется за счет защиты от окислительного, токсического и других форм клеточного стресса, ускорения созревания яйцеклеток [30,31].…”
unclassified
“…Данный эффект блокируется конкурентным антагонистом рецепторов мелатонина, люзиндолом, в частности в нервных стволовых клетках и плюрипотентных стволовых клетках [29]. На уровне тотипотентных стволовых клеток действие МТ реализуется за счет защиты от окислительного, токсического и других форм клеточного стресса, ускорения созревания яйцеклеток [30,31].…”
unclassified
“…It is of paramount importance to note that melatonin levels and its receptors significantly and gradually decline in several organs over the life-span [ 9 , 10 ], which may favor both the progression of ageing, and the increased risk of suffering different pathologies. In this regard, there are many and varied studies that show that the exogenous administration of melatonin can be beneficial for dealing with different diseases and pathological and/or degenerative conditions [ 9 , 11 , 12 , 13 ]. Among the different published works, the revision study carried out by Wang and collaborators (2022) is noteworthy, in which the current evidence of the application of melatonin not only on periodontal treatment, but also on periodontitis-related systemic comorbidities is discussed.…”
mentioning
confidence: 99%
“…Recently, we have demonstrated that melatonin induces a recovery in the functionality of adult hippocampal neurogenesis in aged and neurodegenerative brains of mice with accelerated senescence [ 13 ]. In this respect, Sun and collaborators (2022) also showed that melatonin promotes antler growth in sika deer by accelerating MT1-mediated mesenchymal cell differentiation and inhibiting VEGF-induced degeneration of chondrocytes [ 20 ].…”
mentioning
confidence: 99%